Spillovers among sovereign debt markets: Identification by absolute magnitude restrictions - Roberto A. De Santis; Srĕcko Zimic (European Central Bank (ECB), 2017)
This paper studies spillovers among US and European sovereign yields. We provide a new method based on absolute magnitude restrictions of the impact matrix to identify the countries that were the main sources of spillovers. Despite the large size of shocks from euro area stressed countries, connectedness among sovereign yields declined between 2008 and 2012 due to financial fragmentation, particularly between countries with more divergent business and fiscal cycles. We show that none of the sovereign yields are insulated from foreign shocks and that shocks to the Greek bond market in 2010 explained 20-30% of the variance of sovereign yields in stressed countries, while in 2011-2012 Italy (not Spain) was the source of systemic risk.
Keywords: C3; G2; 330; Spillovers; Contagion; Connectedness; Fragmentation; Sovereign Risk; SVAR identification